The Value of Liberal Feminism in “Sì” Giorgio Armani Perfume Line Advertisement - Tjiang Jennifer Chandra; Liliek Soelistyo (Institute of Research and Community Outreach - Petra Christian University, 2023)
This study aims to find out how verbal communication and visual signs in the